Sustainability Practices in Accommodation Facilities Across Czech Tourism Destinations - Vávrová, Jitka; Červová, Lenka; Brandová, Blanka; Dembicka-Niemiec, Agnieszka (Journal of Tourism, Sustainability and Well-being, 2025)
This study aims to investigate the existence of statistically significant variations in sustainability practices among accommodation facilities in different tourism destinations in the Czech Republic. Data was collected from 429 collective facilities listed on Booking.com, selected in proportion to the most frequently visited regions. The analysis involved Chi-square tests and one-way ANOVA. The research revealed notable variations in sustainability practices among different tourism destinations, with mountainous areas prioritising nature conservation and urban settings focusing more on water preservation. The findings contribute to understanding the destination-specific sustainability approaches and the importance of considering environmental and cultural resources in developing tourism destinations.